1987
DOI: 10.1002/cyto.990080507
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of DNA in cells obtained from deparaffinized formalin‐fixed lymphoid tissues

Abstract: Flow cytometric analysis of DNA content was performed on nuclear suspensions prepared from fresh and from paraffin-embedded, formalin-fixed lymphoid tissues. We confirmed previous reports that it is possible to obtain nuclear suspensions from deparaffinized, formalin-fixed tissues, suitable for DNA analysis by flow cytometry. We observed a tendency for a larger coefficient of variation (CV) of the DNA measurements in the fixed tissues than in the unfixed material causing abnormalities in 2 of 19 lymphomas to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…IAN --+---A f-ID ------A ..,.+11. AilOl--C (Bauer et al, 1986;McIntire et al, 1987), but not by others (Camplejohn & Macartney, 1985), and raises the possibility that the larger values of CV may mask minor degrees of aneuploidy. However, a comparative study of flow cytometric DNA analysis using fresh tissue (median CV = 3.1) and paraffin embedded tissue (median CV = 6.1) showed consistent identification of ploidy status in 33/35 tumours.…”
Section: Resultsmentioning
confidence: 97%
“…IAN --+---A f-ID ------A ..,.+11. AilOl--C (Bauer et al, 1986;McIntire et al, 1987), but not by others (Camplejohn & Macartney, 1985), and raises the possibility that the larger values of CV may mask minor degrees of aneuploidy. However, a comparative study of flow cytometric DNA analysis using fresh tissue (median CV = 3.1) and paraffin embedded tissue (median CV = 6.1) showed consistent identification of ploidy status in 33/35 tumours.…”
Section: Resultsmentioning
confidence: 97%
“…Other cell kinetic variables such as mitotic index (Akerman et af., 1987) or flow cytometric Sphase cell fraction (Braylan et al, 1980, Scarffe andCrowther, 1981;Roos et al, 1985;Christensson et al, 1986;Macartney et al, 1986;Lenner et al, 1987;McIntire et al, 1987;Griffin et al, 1988) have been shown to be indicators of clinical aggressiveness. However, in these studies the survival curves of the two kinetic subgroups become similar after some years, whereas in our study they still appeared markedly different after 6 years.…”
Section: Discussionmentioning
confidence: 97%
“…Different methods, based on measurement of in vitro [3H]-thymidine (Steel, 1977) or bromodeoxyuridine (Gratzner, 1982) incorporation, on flow cytometric DNA content (Baisch et al, 1982) or on immunocytochemical detection of markers supposed to identify cycling cells (Gerdes et al, 1983), have been used to determine proliferative activity. Previous studies have shown that a high proliferating cell fraction determined by any of the different approaches is likely to be associated with high-grade malignancy histology and with a poor prognosis (Silvestrini et al, 1977;Braylan et al, 1980;Brandt et al, 1981;Costa et al, 1981;Scarf€e and Crowther, 1981;Gerdes et al, 1984Gerdes et al, , 1987Roos et al, 1985;Christensson et al, 1986;Del Bino et al, 1986;Macartney er al., 1986;Akerman et al, 1987;Gerdes et al, 1987;Lenner et al, 1987;McIntire et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…All previous studies [9,11,12,17] relied on paraffin-embedded tis sues which offer the possibility for retrospective studies relating DNA ploidy to patient survival and prognosis. However, this approach suffers from a number of limita tions: the overall quality of DNA histograms of paraffinembedded tissue is generally inferior to that obtained with fresh tissue [13], and the DNA stability of tissue extracted from paraffin may vary from one specimen to another [ 12]. It was therefore decided to limit the present study to unfixed frozen tissues of which some specimens had been stored at -7 0 °C for up to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an attempt to overcome the reported difficulties associated with the use of paraffinembedded tissue for flow cytometric DNA determina tions [12,13], the present study was confined to unfixed frozen tissue.…”
Section: Introductionmentioning
confidence: 99%